Male Androgenetic Alopecia Treated with Single Spin Platelet Rich Plasma: A Case Report - Anggi Anastasia Ursula Dien; Ferra Olivia Mawu; Aryani Adji; William Yudistha Anggawirya; Paulus Mario Christopher (Green Publisher Indonesia, 2025)
Androgenetic alopecia (AGA) is the most common type of hair loss, causing gradual, progressive miniaturization of hair follicles and shortening of the anagen phase in genetically predisposed men and women, following a distinct pattern. Hair loss usually begins after puberty and is more prevalent in men. This case report details a young male patient with androgenetic alopecia treated with single spin platelet-rich plasma (PRP) therapy combined with topical minoxidil. A 27-year-old Minahasan male experienced hair thinning and loss for 10 years, starting at the middle of his head and spreading outward. Examination showed thinning at the fronto-parietal hairline and vertex, classified as Hamilton-Norwood III vertex. Treatment involved biweekly single spin PRP injections and twice-daily application of 5% topical minoxidil. The PRP was prepared by centrifugation at 3000 rpm for 15 minutes, with up to nine sessions administered. Clinical evaluations through hair pull tests and trichoscopy revealed significant improvement, including increased hair density and changes in follicle diameter in treated areas. By week eighteen, hair density increased markedly, and hair loss diminished without side effects. The patient was highly satisfied with the cosmetic results. This case report indicates that single spin PRP combined with topical minoxidil is an effective, safe, and reliable treatment for male androgenetic alopecia, offering clinical improvement and enhanced hair growth without adverse effects. The simplified PRP protocol provides practical advantages for clinical use, especially in resource-limited settings, and supports growing evidence for PRP as an adjunct therapy for androgenetic alopecia in young Asian patients.